ANALISIS EKONOMI SUSU PASTEURISASI DENGAN PENAMBAHAN REMPAH-REMPAH DAN UJI TOTAL PLAT COUNT DENGAN WAKTU SIMPAN YANG BERBEDA: ECONOMIC ANALYSIS OF PASTEURIZED MILK WITH ADDITIONAL SPICES AND TOTAL PLATE COUNT TEST WITH DIFFERENT STORAGE TIME - Jamil, Rohmad Maulidin; Abdurrahman, Zakaria Husein; Nefasa, Angela Nitia (Universitas Boyolali, 2022)
The purpose of this study was to determine the interaction of adding spices and storage time to the total number of microorganisms in pasteurized milk and its feasibility. The ingredients used were 7.4 l of fresh cow's milk, 0.5 kg of sugar, 37 g of powdered ginger, 3.7 g of cinnamon powder, 37 g of turmeric powder, and aquades. The first step in making pasteurized milk is filtering fresh milk, then dividing the milk into two parts. The first part is made into pasteurized milk without the addition of spices, the second part is made into pasteurized milk with the addition of spices. When the second part of the milk reaches a temperature of 40°C then the spices are mixed into the milk until well blended. If the temperature reaches 63°C for 30 minutes, then turn off the heat and wait for the temperature of the milk to drop. Then the milk is packed into 100 ml bottles. The packaging of the first part of milk without the addition of 37 sample bottles of spices and the second part of pasteurized milk with the addition of 37 sample bottles of spices. Total Plate Count (TPC) test used a factorial completely randomized design (CRD) with four repetitions. The data obtained were then processed by analysis of variance ANOVA, to determine the interaction between milk with the addition of spices and different storage times. The results of the TPC test showed that the addition of spices to pasteurized milk had no significant effect after pasteurization was carried out (P>0.01) but had a significant effect (P<0.01) on the total microorganisms in different storage times. The results of the calculation of economic analysis show that a Break Even Point (BEP) with a profit of 10% produces a BEP unit of 485 units of BEP of 6,270,000 rupiah and reaches the break-even point at 0.3 months. The profit per day is 86,950 rupiah with 312 working days, the net profit per year is 27,128,400 rupiah and the time needed to return the initial capital is 0.03 years.